How to be a student 100 great ideas and practical habits for students everywhere - Moore, Sarah (Sarah M.) (Open University Press, 2005)
Helps students to tackle a wide range of challenges and opportunities associated with life at college. It provides 100 actionable reflections, ideas, strategies, and tactics that can help readers to make the most of their time in college, such as developing study rituals, getting help when it's needed, getting to know librarians and lurking in the library, reading, and being a critical learner